Rosmarinic acid protects mice from imiquimod induced psoriasis‐like skin lesions by inhibiting the IL‐23/Th17 axis via regulating Jak2/Stat3 signaling pathway. (18th May 2021) - Zhang, Miaomiao; Li, Ning; Cai, Ruhang; Gu, Jiangyong; Xie, Fuda; Wei, Hong; Lu, Chuanjian; Wu, Dinghong
Abstract : IL‐23/Th17 (IL‐17) axis plays a critical role in psoriasis. Rosmarinic acid (RA) was proved the inhibitory effect of T cell infiltration in the skin. However, whether and how RA has beneficial effects on psoriasis did not really know yet. So lipopolysaccharide (LPS)‐induced abnormal proliferation Hacat cell line and Imiquimod (IMQ)‐induced psoriasis‐like mouse dermatitis were used to assess the pharmacological effects and mechanisms of RA by Psoriasis Area Severity Index (PASI) score, histopathology, flow cytometry, reverse transcription‐polymerase chain reaction (RT‐PCR) and western blotting. The results showed that RA inhibited LPS‐induced aberrant expression of Hacat cell line, and significantly alleviated IMQ‐induced skin inflammation. Although RA had no obviously effect on the ratio of epidermal Langerhans cell (LC) and LC migration from the skin to the skin draining lymph nodes, RA inhibited the expression of IL‐23 in skin lesions, as well as reduced the differentiation of Th17 cells and producing of IL‐17A by down regulating the transcriptor factor RORγt and JAK2/Stat3 signal pathway, comparing to IMQ treated group. The findings suggest that RA inhibits psoriasis‐like skin inflammation in vivo and in vitro by reducing the expression of IL‐23, inhibiting Th17 dominated inflammation and down regulating the Jak2/Stat3 signal pathway.